2016
DOI: 10.1007/s11748-016-0738-9
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation following aortic valve replacement: impact of perioperative use of intravenous β-blocker

Abstract: POAF frequently occurred in patients undergoing AVR, and was significantly related to prolonged ICU stay and postoperative stroke. Our findings show that advanced age and absence of preoperative β-blocker usage are risk factors for POAF. Furthermore, in patients undergoing AVR, perioperative intravenous β-blocker administration may be useful for prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
5
1
3
Order By: Relevance
“…The optimal strategy seems to initiate oral beta-blocker pre-operatively and start landiolol intra-operatively or in the ICU. One retrospective study 44 showed that preoperative oral beta-blockade associated with landiolol is superior to landiolol started alone post-operatively. On the other hand, transition to oral beta-blocker may be necessary if landiolol infusion is stopped early, with patient discharged from ICU.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…The optimal strategy seems to initiate oral beta-blocker pre-operatively and start landiolol intra-operatively or in the ICU. One retrospective study 44 showed that preoperative oral beta-blockade associated with landiolol is superior to landiolol started alone post-operatively. On the other hand, transition to oral beta-blocker may be necessary if landiolol infusion is stopped early, with patient discharged from ICU.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Tieto výsledky korelujú s prácou autorov Yokota a spol., ktorí prezentujú, že čas CPB, LVEF ani COPD nie sú rizikovými faktormi vzniku POAF. 13 Kohno a spol. taktiež nenašli žiadnu koreláciu medzi celkovým časom chirurgického výkonu, časom CPB alebo časom svorky aorty a vznikom POAF počas AVR.…”
Section: Diskusiaunclassified
“…13 Literárne údaje uvádzajú pooperačnú ap-likáciu-blokátorov ako protektívny faktor vzniku POAF, pričom vynechanie dlhodobej aplikácie -blokátorov na druhej strane riziko vzniku POAF zvyšuje. 8,13 Aj Yokota a spol. uvádzajú pooperačnú aplikáciu -blokátorov ako protektívny faktor vzniku POAF.…”
Section: Diskusiaunclassified
See 1 more Smart Citation
“…Studies showed that POAF could lead to a longer hospital stay and a greater incidence of other complications [2]. POAF risk is higher among patients who are older [3], racial/ethnic minorities [4], taking perioperative medications such as β-blocker [5], and having hypertension [6] or operative trauma [7].…”
Section: Introductionmentioning
confidence: 99%